PENGUATAN KOMPETENSI METODOLOGI PENELITIAN EVALUASI BAGI PRAKTISI PENDIDIKAN INDONESIA MELALUI WEBINAR NASIONAL - Iqbal, Muhammad; Hardiansyah, Rila; Ridlo, M. Rasyid; Hakim, Lukmanul (LPPM Universitas Nusa Mandiri, 2026)
Competency in evaluation research methodology remains limited among Indonesian education practitioners, yet its documentation through national webinars has received insufficient attention in the literature. This article aims to report the implementation and evaluate the outcomes of a national webinar titled “Evaluation Research Methodology: Between Paradigms, Approaches, Methods, and Implementation” as a community service activity using a descriptive evaluative approach. Participant data from an electronic registration form were analyzed using descriptive statistics. A total of 898 participants from 35 provinces joined via Zoom and YouTube Live, comprising predominantly students (64.48%), lecturers (16.48%), and teachers (15.26%), mostly from higher education institutions (62.25%) and Education/Teacher Training disciplines (42.87%). The webinar successfully enhanced participants’ conceptual understanding of evaluation research paradigms, quantitative-qualitative-mixed approaches, key evaluation models (CIPP, Kirkpatrick, Goal-Oriented), and systematic research stages, demonstrating the efficacy of webinars in reaching a national audience for professional capacity building. These findings underscore the need for sustainable development programs, communities of practice, and integration of evaluation research methodology into higher education curricula, thereby contributing to SDG 4 on quality education.